Environmental awareness and environmental information disclosure: An empirical study based on energy industry - Wang, Shijin; Zhou, Ziwen; Tian, Keqin (Frontiers in Psychology, 2022)
Environmental protection and governance have become a topic of global concern. Sustainable development and green development are the unshakable ideas of China's social and economic development. Under this premise, the energy industry, as a pillar industry in China, has the disadvantages of high energy consumption and heavy pollution. Therefore, the quality of environmental information disclosure in energy industry needs to be improved urgently. This paper selects 66 samples from 22 energy companies in Shanghai and Shenzhen stock markets from 2018 to 2020 as the research object, establishes two potential variables and 13 observed variables of environmental awareness and environmental information disclosure respectively, and constructs structural equation model to study the impact of corporate environmental awareness on environmental information disclosure.The research shows that the environmental awareness of enterprises is positively related to the level of environmental information disclosure. The conclusion is helpful to improve the enthusiasm and consciousness of energy companies to disclose environmental information. A better role in supervising the quality of environmental information disclosure by the government, enterprises and the public can be played.